Moving On New York City Ballet after Balanchine - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2008)
New York City Ballet after Balanchine. Damian Woetzel is a star and Wheeldon's Carousel (A Dance) proves that he doesn't care who knows it.